Pengaruh Koneksi Politik terhadap Nilai Perusahaan - Evalestine Patriarini, Winny (E-Jurnal Akuntansi; Vol 30 No 6 (2020), 2020)
The purpose of this study is to analyze the effect of political connection on firm value. This study uses 160 samples listed on the Indonesia Stock Exchange for the period 2014 to 2018. The analysis used in this study is the Multiple Regression analysis model that is processed with SPSS 20 software. This study found that political connections had a positive and significant effect on firm value. The results show that the political connections that a company has can cause a company to have an advantage so that it can increase the value of the company. Keywords: Political Connection; Firm Value.